2017
DOI: 10.14744/anatoljcardiol.2017.7716
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neutrophil-to-lymphocyte ratios in postcardiac arrest patients treated with targeted temperature management

Abstract: Objective:The prognostic value of changes in neutrophil-to-lymphocyte ratios (NLR) in cardiac arrest survivors receiving targeted temperature management (TTM) is unknown. The current study investigated NLR in postcardiac arrest (PCA) patients undergoing TTM.Methods:This retrospective single-center study included 95 patients (59 males, age: 55.0±17.0 years) with in-hospital and out-of-hospital cardiac arrests who underwent TTM for PCA syndrome within 6 h of cardiac arrest. Hypothermia was maintained for 24 h at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Because a widely inflammatory process is triggered in patients with CA, previous studies have frequently investigated the importance of inflammatory markers. [16][17][18][19][20] NLR, a cheap and an easily detectable marker from CBC, is a combination of two independent markers of systemic inflammation. 5 It was demonstrated that NLR was a stronger parameter than other white blood cell subtypes for evaluating the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a widely inflammatory process is triggered in patients with CA, previous studies have frequently investigated the importance of inflammatory markers. [16][17][18][19][20] NLR, a cheap and an easily detectable marker from CBC, is a combination of two independent markers of systemic inflammation. 5 It was demonstrated that NLR was a stronger parameter than other white blood cell subtypes for evaluating the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Because a widely inflammatory process is triggered in patients with CA, previous studies have frequently investigated the importance of inflammatory markers 16‐20 . NLR, a cheap and an easily detectable marker from CBC, is a combination of two independent markers of systemic inflammation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the relationship between lymphopenia in the acute phase and prognosis of PCAS patients was reported. One study showed that the neutrophil–lymphocyte ratio (NLR) is associated with mortality in cardiac arrest patients at admission . Another study showed that lymphopenia occurs in PCAS patients at admission and is associated with neurological recovery in out‐of‐hospital cardiac arrest patients .…”
Section: Introductionmentioning
confidence: 99%
“…Baser et al [61] investigated the relationship between neutrophil cells and mortality risk prediction and emphasized that vasopressors are used in patients who survive.…”
Section: Discussionmentioning
confidence: 99%